Basic statistics using Excel and MegaStat - Orris, J. B (McGraw-Hill Irwin, 2007)
Offers an Excel-focused approach to using statistics in business. This work illustrates statistical concepts with applied examples. It introduces modern computing tools and applications, and presents statistical concepts as applied using Excel. It also enables students to take advantage of Excel to develop and drive problem-solving skills.